Evaluation of the effect of Beauveria bassiana in the biological control of Varroa destructor, a parasite of honey bees (Apis mellifera) at the Felisa farm at the municipality of Patios, Norte de Santander. - Chacin Zambrano, Christian; Duarte, Francy Liliana; Reyes, Lisbeth Carolina (Innovaciencia, 2013)
Beekeeping is an activity that produces significant benefits to agriculture and the environment; Through the pollination action of bees helps to increase productivity as well as biodiversity in the ecosystem. In recent years, has significantly increased prevalence of parasites in this species, particularly the Varroasis, a disease caused by the mite Varroa destructor. The causal agent produces losses between 30% and 50% of total production and in turn can cause damage to the quality of honey by the excessive use of chemicals for disease control and the slow and progressive deterioration health of producers. Noting this, we evaluated the incidence of fungus Beauveria bassiana in natural populations of Varroa destructor in acarofauna associated, and the remains of the hive by pathogenicity tests in laboratory conditions to evaluate the effect of the biocontrol entomopathogenic then enter in apiaries infected with the disease. According to the results obtained in the adult infestation of V. destructor in Apis mellifera Africanized sampling Felisa made on the farm in the municipality of Los Patios, recorded rates of infestation in hives from 3.4% to 8.3% on the infection status of breeding was 4.5% to 13.7%. In laboratory tests it was possible to observe that the fungus B. bassiana attacked by an effective control mites without harming bees, propolis and honey allowing the insect to continue their normal activities, controlling the disease in a biological, not chemical.